Difficulties present in adhering to partner prenatal care worldwide: An integrative review - Batista, Walesca Carvalho Amaral (2021)
Objective: To identify through scientific productions the factors that intervene in adherence to the partner's prenatal care in the last ten years. Method: an integrative review was carried out in the following databases: Scientific Eletronic Library Online (SciELO); Latin American and Caribbean Literature on Health Sciences (LILACS); Medical Literature Analysis and Retrieval Sistem Online (MEDLINE); and Cumulative Index to Nursing and Allied Health Literature (CINAHL). Result: Among the 07 articles found, 05 were made in Brazil, in the years 2010, 2012, 2017 and 2018; and 02 were published in England in the years 2013 and 2015. The factors that intervene in the partner's prenatal adherence in the last ten years were grouped into two (2) categories: a) Man / father's experience during the pre- natal and b) No presence of the man / father during the prenatal period. Conclusion: Even with the identification of the man's will to want to participate in this process and prepare for the birth of the child, however, in Brazil there are still cultural and institutional barriers that prevent him from realizing his right. In other developed countries, on the other hand, most partners were very positive about pregnancy, present in prenatal care and aware of their rights to paternity leave.